Implementation of a patient-centered remote wound monitoring system for management of diabetic foot ulcers - Keegan, Alana C.; Bose, Sanuja; McDermott, Katherine M.; Starks White, Midori P.; Stonko, David P.; Jeddah, Danielle; Lev-Ari, Eilat; Rutkowski, Joanna; Sherman, Ronald; Abularrage, Christopher J.; Selvin, Elizabeth; Hicks, Caitlin W. (Frontiers in Endocrinology, 2023)
Background: Regular clinical assessment is critical to optimize lower extremity wound healing. However, family and work obligations, socioeconomic, transportation, and time barriers often limit patient follow-up. We assessed the feasibility of a novel, patient-centered, remote wound management system (Healthy.io Minuteful for Wound Digital Management System) for the surveillance of lower extremity wounds. Methods: We enrolled 25 patients from our outpatient multidisciplinary limb preservation clinic with a diabetic foot ulcer, who had undergone revascularization and podiatric interventions prior to enrollment. Patients and their caregivers were instructed on how to use the digital management system and asked to perform one at-home wound scan per week for a total of 8 weeks using a smartphone application. We collected prospective data on patient engagement, smartphone app useability, and patient satisfaction. Results: Twenty-five patients (mean age 65.5±13.7 years, 60.0% male, 52.0% Black) were enrolled over 3 months. Mean baseline wound area was 18.0±15.2 cm2, 24.0% of patients were recovering from osteomyelitis, and post-surgical WIfI stage was 1 in 24.0%, 2 in 40.0 %, 3 in 28.0%, and 4 in 8.00% of patients. We provided a smartphone to 28.0% of patients who did not have access to one that was compatible with the technology. Wound scans were obtained by patients (40.0%) and caregivers (60.0%). Overall, 179 wound scans were submitted through the app. The mean number of wound scans acquired per patient was 0.72±0.63 per week, for a total mean of 5.80±5.30 scans over the course of 8 weeks. Use of the digital wound management system triggered an early change in wound management for 36.0% of patients. Patient satisfaction was high; 94.0% of patients reported the system was useful. Conclusion: The Healthy.io Minuteful for Wound Digital Management System is a feasible means of remote wound monitoring for use by patients and/or their caregivers.